PENINGKATAN PENGETAHUAN KONSUMEN DAN SOSIALISASI MAKANAN HALAL DAN TOYIB DI SEKOLAH DASAR MUHAMMADIYAH 3 WIROBRAJAN, YOGYAKARTA: PENINGKATAN PENGETAHUAN KONSUMEN DAN SOSIALISASI MAKANAN HALAL DAN TOYIB DI SEKOLAH DASAR MUHAMMADIYAH 3 WIROBRAJAN, YOGYAKARTA - ahda, mustofa; Kusbandari, Aprilia; Pangastuti, Palupi Melati (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2022)
Government regulations require halal product distribution in Indonesia have been regulated in the Halal product law No 33 in 2014. Based on these rules, all producers have to market and distribute halal goods. The goal of halal is to produce healthy food. However, the big problem is that this rule has not been fully realized. In 2021, many products are not clear whether they are halal or not. Therefore, the socialization of halal food for consumers is very important to support government regulations. In this case, the consumers who are in a religious environment from one of the big Islamic organizations. The Basic score of consumers’ knowledge is very good, they have a score above 75. After promotion, the consumers’ knowledge increased. Besides, consumers also understand food additives. Based on these results, the government should drive the consumers and producers to pay attention to their religion because it can increase awareness of halal and toyib products.